2021
DOI: 10.3390/diagnostics11112014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Parameters in Quadriceps Muscle Were Associated with Clinical Features and Muscle Strength of Women with Rheumatoid Arthritis: A Cross-Sectional Study

Abstract: Background: Rheumatoid arthritis (RA) is an autoimmune, inflammatory and chronic disease that may lead to loss of muscle mass, muscle strength and decreased functionality. Our objectives are to assess the quadriceps muscle morphology by ultrasound (MU) and verify its associations with clinical features, muscle strength and physical function in RA patients. Methods: In this cross-sectional study, RA women (≥18 years) were included. Morphological parameters in quadriceps muscle consisted of the muscle thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that muscle ultrasound can be used successfully to detect changes in both muscle mass and quality in a variety of clinical conditions, such as chronic kidney disease, cirrhosis, rheumatoid arthritis, and hip fracture. [28][29][30][31] So far, there have been two studies on the use of muscle ultrasound in diabetic patients. Tan et al found that muscle thicknesses of rectus femoris (RF), vastus intermedius (VI), vastus medialis (VM) and vastus lateralis (VL) and pennate angle of VI and VM were significantly lower in type 1 diabetes than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that muscle ultrasound can be used successfully to detect changes in both muscle mass and quality in a variety of clinical conditions, such as chronic kidney disease, cirrhosis, rheumatoid arthritis, and hip fracture. [28][29][30][31] So far, there have been two studies on the use of muscle ultrasound in diabetic patients. Tan et al found that muscle thicknesses of rectus femoris (RF), vastus intermedius (VI), vastus medialis (VM) and vastus lateralis (VL) and pennate angle of VI and VM were significantly lower in type 1 diabetes than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We report a significant correlation between the lower extremity muscle thickness in patients with incomplete spinal cord injury and functional scores in terms of LEMS, FIM motor, FIM walk, and WISCI II scores. Muscle thickness is believed to be a reproducible measure of muscle mass and hence has been thought to influence functional measures [ 37 , 38 , 39 ]. One possible explanation for our findings is that the participants who had a higher LEMS or ambulatory score were able to weight-bear through the affected lower extremities, activating the anti-gravity lower extremity muscles and attenuating the degree of muscle atrophy, and hence had a larger muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another research looked at the relationship between quadriceps muscle US morphology (muscle thickness and pennation angle) and clinical characteristics, muscular strength (grip strength test) and physical function (HAQ, TUG test) in 55 women with RA [ 82 ]. Unlike the previous trial, this research supported the use of US in detecting RA patients with impaired muscular strength and physical function.…”
Section: Introductionmentioning
confidence: 99%